Digital Media Promote the Development of Creative Industry: Take Traditional Culture and Intangible Heritage as an Example - Zhao, Yanjun (Transactions on Social Science, Education and Humanities Research, 2024)
Nowadays, an increasing number of individuals realize the significance of preserving the promoting traditional cultural and intangible heritage. This phenomenon has gained significant attention in recent years, and this paper aims to synthesize the existing research. The research goal for this paper is to delve into the literature of digital media and the creative industry, with a focus on understanding its impact on its role and application. Through the analysis, this paper hopes to contribute new insights to the existing research on the propaganda of traditional culture and intangible heritage by using social media. Specifically, the essay aims to foster a deeper understanding and appreciation of traditional culture. It is found that social media primarily has positive effects on promotion of intangible heritage. Social builds a bridge between the individuals and traditional culture, making more people know about the intangible heritage. With the findings, the study contributes to the preservation and revitalization of traditional culture in the digital era.